The AT1 Receptor Antagonist Losartan Does Not Affect Depressive-Like State and Memory Impairment Evoked by Chronic Stressors in Rats - Costa-Ferreira, Willian; Morais-Silva, Gessynger; Gomes-de-Souza, Lucas; Marin, Marcelo T.; Crestani, Carlos C. (Frontiers in Pharmacology, 2019)
The present study investigated the effect of the treatment with the angiotensin II type 1 receptor (AT1) antagonist losartan in the depressive-like state and memory impairment evoked by exposure to either homotypic (i.e., repeated exposure to the same type of stressor) or heterotypic (i.e., exposure to different aversive stimuli) chronic stressors in rats. For this, male Wistar rats were subjected to a 10 days regimen of repeated restraint stress (RRS, homotypic stressor) or chronic variable stress (CVS, heterotypic stressor) while being concurrently treated daily with losartan (30 mg/kg/day, p.o.). Depressive-like state was evaluated by analysis of the alterations considered as markers of depression (decreased sucrose preference and body weight and coat state deterioration), whereas cognitive non-emotional performance was tested using the novel object recognition (NOR) test. Locomotor activity was also evaluated in the open field test. Both RRS and CVS impaired sucrose preference and caused coat state deterioration, whereas only CVS impaired body weight gain. Besides, RRS impaired short-term memory (but not long-term memory) in the NOR test. Neither depressive-like state nor memory impairment evoked by the chronic stressors were affected by the treatment with losartan. Nevertheless, CVS increased the locomotion, which was inhibited by losartan. Taken together, these results provide evidence that the chronic treatment with losartan does not affect the depressive-like state and memory impairment evoked by either homotypic or heterotypic chronic stress regimens in rats.